UPPER CAMBRIAN TRILOBITES AND BRACHIOPODS FROM SEVERNAYA ZEMLYA, ARCTIC RUSSIA, AND THEIR IMPLICATIONS FOR CORRELATION AND BIOGEOGRAPHY - Rushton A.W.A.; Cocks L.R.M.; Fortey R.A. (My University, 2002)
A new Late Cambrian trilobite–brachiopod fauna from the Kurchavinskaya Formation, Severnaya Zemlya, northern Siberia, allows correlation of the Ketyi Horizon of the NW Siberian succession with the praecursor Zone of the Baltic olenid zonation. The presence on Severnaya Zemlya of the typically Siberian trilobite Kujandaspisketiensis indicates that even if Severnaya Zemlya lay on a separate plate, whether Kara or Arctida as postulated by other authors, then it was still probably not far from Siberia. However, the associated brachiopods are partly endemic to Severnaya Zemlya, thus giving some support to the independent palaeomagnetic evidence for their origin on a plate separate from Siberia.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская